Back Cover: Corrole and Porphyrin Amino Acid Conjugates: Synthesis and Physicochemical Properties (Chem. Eur. J. 32/2016). Issue 32 (13th June 2016) - Karikis, Kostas; Georgilis, Evangelos; Charalambidis, Georgios; Petrou, Athanasia; Vakuliuk, Olena; Chatziioannou, Theodore; Raptaki, Iliana; Tsovola, Sofia; Papakyriacou, Ioanna; Mitraki, Anna; Gryko, Daniel T.; Coutsolelos, Athanassios G.
Abstract : Conjugates of amino acids with porphyrins and corroles form well‐defined spherical nanostructures under ambient conditions as illustrated on the cover. The study of their photophysical properties in solid, liquid, and self‐assembled forms revealed the enhancement of their properties due to the formation of spherical morphologies. More information can be found in the Full Paper by A. Mitraki, D. T. Gryko, A. G. Coutsolelos et al. on page11245 .